A boron salt compound, a preparation method thereof, and application of the boron salt compound in iron-catalyzed polymerization of conjugated dienes
Patent Information
- Application Number
- CN202510519030.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的是为了解决现有共轭烯烃聚合体系中的硼盐化合物助催化剂体系溶解性差、制备成本高且聚合物分子量高而导致的聚合体系成本提升的技术问题
[0050](1)本发明提供的硼盐化合物的制备工艺简单、产率高,且制备价格低,传统硼酸盐三苯碳四(五氟苯基)硼酸盐的制备原材料如五氟溴苯的采购价格为48万/吨,本申请的硼酸盐的制备原材料如3,4,5-三氟溴苯的采购价格为30万/吨,3,5-双(三氟甲基)溴苯的采购价格为18万/吨。因此,相比传统硼酸盐,本申请的硼酸盐在制备成本上具有极大的价格优势,利于降低工业化成本。
Smart Images

Figure CN122978149A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of iron-based catalytic polymerization, specifically relating to a boron salt compound, its preparation method, and its application in iron-catalyzed conjugated diene polymerization. Background Technology
[0002] The global annual production of natural rubber is limited by geographical environment, climate conditions and planting cycle, making it difficult to meet the growing demand of modern industry for elastomer materials. Therefore, it is necessary to develop corresponding synthetic rubber catalytic systems.
[0003] The existing production systems for synthesizing diene rubber mainly utilize coordination polymerization catalysts, and efficient co-catalysts are one of the core elements of polyolefin synthesis technology. Currently, the development of such co-catalyst systems shows a significant trend towards diversification. Among them, tetra(pentafluorophenyl)boron salt catalyst systems have received widespread attention from academia and industry due to their high activity since their introduction. However, the raw material costs of these catalysts are generally high; and the co-catalysts obtained from them either have limited solubility or excessively high polymer molecular weight in iron-catalyzed polymerization systems, adversely affecting the industrial production of conjugated diene polymerization. Therefore, there is an urgent need in current industrial production to develop a novel boron salt compound co-catalyst with high solubility, low cost, and a suitable polymer molecular weight to meet the polyolefin industry's production requirements for efficient and economical catalytic systems. Summary of the Invention
[0004] The purpose of this invention is to address the technical problems of poor solubility, high preparation cost, and increased polymerization cost due to the high molecular weight of boron salt co-catalysts in existing conjugated olefin polymerization systems. This invention provides a boron salt compound, its preparation method, and its application in iron-catalyzed conjugated diene polymerization. This boron salt compound enables efficient and controllable polymerization of conjugated dienes.
[0005] The technical solution of the present invention is as follows:
[0006] One objective of this invention is to provide a boron salt compound, wherein the boron salt compound has the following general structural formula:
[0007]
[0008] In the formula, R1, R2, R3, R4, and R5 are each independently selected from one of H, F, Cl, and CF3, and R1, R2, R3, R4, and R5 are not all H at the same time; R6, R7, and R8 are each independently selected from one of phenyl, substituted phenyl, or C6-C30 straight-chain or non-straight-chain alkyl, and the total number of carbon atoms in R6, R7, and R8 is ≥20.
[0009] Preferably, the boron salt compound is selected from one of formulas B1 to B18:
[0010]
[0011]
[0012]
[0013] A second objective of this invention is to provide a method for preparing the above-mentioned boron salt compound, wherein the preparation method is carried out according to the following steps:
[0014] Water and an organic solvent were added to a tetraphenylborate metal salt containing R1, R2, R3, R4, and R5 substituents and an organic amine salt containing R6, R7, and R8 substituents. The mixture was stirred and reacted. After separation, the organic phase was dried and the solvent was removed to obtain the boron salt compound.
[0015] Preferably, in the tetraphenylborate metal salt containing R1, R2, R3, R4, and R5 substituents, each of R1, R2, R3, R4, and R5 is independently selected from one of H, F, Cl, and CF3, and R1, R2, R3, R4, and R5 are not all H; the tetraphenylborate metal salt is at least one of lithium, sodium, and potassium salts. Most preferably, the tetraphenylborate metal salt is a sodium salt.
[0016] Preferably, in the organic amine salt containing R6, R7, and R8 substituents, each of R6, R7, and R8 is independently selected from phenyl, substituted phenyl, and C6-C30 straight-chain or non-straight-chain alkyl groups, and the total number of carbon atoms in R6, R7, and R8 is ≥20; the organic amine salt is at least one of organic amine hydrochloride, organic amine sulfate, and organic amine nitrate. Most preferably, the organic amine salt is an organic amine hydrochloride.
[0017] Preferably, the organic solvent is one or more selected from n-hexane, cyclohexane, dichloromethane, toluene, and ethylbenzene. Most preferably, it is dichloromethane.
[0018] Preferably, the molar ratio of the substituted tetraphenylborate metal salt to the substituted organic amine salt is (1-3):1; more preferably, the molar ratio is 1:1.
[0019] Preferably, the stirring reaction temperature is 0-100°C; more preferably, the stirring temperature is 25°C.
[0020] Preferably, the stirring time is >5 min; more preferably, the stirring time is 30 min.
[0021] The third objective of this invention is to provide an application of the above-mentioned boron salt compound as a co-catalyst in iron-catalyzed conjugated diene polymerization.
[0022] The polymerization method steps are as follows:
[0023] Under anhydrous and oxygen-free conditions, solvent, conjugated diene monomer, alkyl aluminum, iron catalyst and boron salt compound are added sequentially to the reactor. The polymerization reaction is carried out by stirring at 0-100℃ for 10-120 min. After the reaction is completed, quencher and anti-aging agent are added. After washing, the mixture is vacuum dried to constant weight to obtain the conjugated diene polymer.
[0024] Preferably, the general structural formula of the iron catalyst is:
[0025]
[0026] Among them, R9, R 10 It is one of hydrogen, alkyl, substituted alkyl, aryl, or substituted aryl, where X is isooctanoic acid (EHA-) or neodecanoic acid (NDA-), and EHA- is... NDA - for More preferably, the iron catalyst has one of the following structures:
[0027]
[0028] Preferably, the alkyl aluminum is one or more selected from diethylaluminum monochloro, diethylaluminum dichloro, trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, triisobutylaluminum, triisopropylaluminum, and diisobutylaluminum hydride; more preferably, the alkyl aluminum is one or more selected from triethylaluminum and triisobutylaluminum; most preferably, it is triethylaluminum.
[0029] Preferably, the conjugated diene monomer is at least one of 1,3-butadiene, isoprene, and bio-based terpenes.
[0030] More preferably, the bio-based terpene is a monoterpene or a sesquiterpene.
[0031] More preferably, the monoterpene is at least one of α-myrcene and β-myrcene, and the sesquiterpene is at least one of α-farnesene and β-farnesene;
[0032] More preferably, the monoterpene is β-myrcene and the sesquiterpene is β-farnesene.
[0033] Preferably, the solvent is one or more of toluene, xylene, chlorobenzene, petroleum ether, n-hexane, and cyclohexane; more preferably, the solvent is cyclohexane.
[0034] Preferably, the volume ratio of solvent to monomer is (1-15):1; more preferably, the volume ratio of solvent to monomer is (3-10):1; and most preferably, the volume ratio of solvent to monomer is 10:1.
[0035] Preferably, the molar ratio of the monomer to the iron catalyst is (100-50000):1; more preferably, the molar ratio of the monomer to the iron catalyst is (1000-25000):1; and most preferably, the molar ratio of the monomer to the iron catalyst is 15000:1.
[0036] Preferably, the molar ratio of boron in the boron salt compound to iron in the iron catalyst is (0.1-20):1; more preferably, the molar ratio of boron in the boron salt compound to iron in the iron catalyst is (0.1-1):1; most preferably, the molar ratio of boron in the boron salt compound to iron in the iron catalyst is 0.3:1.
[0037] Preferably, the molar ratio of aluminum in the alkylaluminum to iron in the iron catalyst is (10-100):1; more preferably, the molar ratio is (20-60):1. Most preferably, the molar ratio is 40:1.
[0038] Preferably, the reaction temperature is 30–90°C and the reaction time is 30–120 min; more preferably, the reaction temperature is 40°C and the reaction time is 60 min.
[0039] The fourth objective of this invention is to provide a rubber material obtained by the above-mentioned application method, wherein the number average molecular weight of the rubber material is 200,000 g / mol to 1,000,000 g / mol, the molecular weight distribution is 1.5 to 5.0, the molar content of 3,4-structure in the conjugated diene polymer unit is 30 to 80% and / or the molar content of 1,2-structure is 30 to 60%, and the glass transition temperature of the raw rubber is in the range of -80 to 10°C.
[0040] Preferably, the rubber material has a molecular weight distribution of 2.5-2.9, the molar content of 3,4-structure in the conjugated diene polymer unit is 34-80% and / or the molar content of 1,2-structure is 58-61%, and the glass transition temperature of the raw rubber is in the range of -70 to -6℃.
[0041] The fifth objective of this invention is to provide a vulcanization method for the above-mentioned rubber material, wherein the method includes:
[0042] Weigh out 100 parts by weight of conjugated diene polymer, 50-150 parts of silica, 1-60 parts of carbon black, 1-3 parts of vulcanizing accelerator, 0.1-10 parts of vulcanizing agent, and 1-5 parts of zinc stearate, mix and knead.
[0043] Preferably, the carbon black is one or more of N660, N550, N324, N330, and N110.
[0044] Preferably, the vulcanizing agent is one or more of TMTD, CZ, M, ZDMC, and ZBX.
[0045] Preferably, the vulcanizing agent is sulfur.
[0046] The sixth objective of this invention is to provide a vulcanized rubber prepared by the above method, wherein the vulcanized rubber has a tensile strength > 16 MPa, an elongation at break > 300%, and a stress at 300% constant elongation > 6 MPa.
[0047] Preferably, the vulcanized rubber has a tensile strength > 17 MPa, an elongation at break > 450%, and a stress at 300% constant elongation > 8 MPa.
[0048] The seventh objective of this invention is to provide an application of the vulcanized rubber prepared by the above method in tire manufacturing, noise reduction and damping, and shock absorption.
[0049] The advantages of this invention compared to existing technologies are:
[0050] (1) The boron salt compounds provided by this invention have a simple preparation process, high yield, and low preparation cost. The raw materials for the preparation of traditional borates, such as triphenylcarbazo(pentafluorophenyl)borate, cost RMB 480,000 per ton, while the raw materials for the preparation of the borates of this application, such as 3,4,5-trifluorobromobenzene, cost RMB 300,000 per ton and 3,5-bis(trifluoromethyl)bromobenzene, cost RMB 180,000 per ton. Therefore, compared with traditional borates, the borates of this application have a significant price advantage in preparation cost, which is conducive to reducing industrialization costs.
[0051] (2) The trifluoromethyl group in the boron salt compound provided by the present invention has a lower electron-withdrawing ability than the fluorine atom. At the same time, compared with pentafluorobromobenzene, the 3,5-bis(trifluoromethyl)bromobenzene of the present application contains more carbons. Therefore, the co-catalyst of the present application not only has a lower electron-withdrawing ability, but also has higher solubility in the polymerization system, which further promotes the efficient progress of the polymerization reaction and ensures a high monomer conversion rate.
[0052] (3) The boron salt compound provided by the present invention has a better polymerization control effect. When 0.3 equivalents of the boron salt compound of the present invention are added and the monomer concentration reaches 15%, the flowability of the polymer product is still better. The molecular weight of the polymer product is significantly lower than that of the polymer product obtained by traditional boron salt compound. The reduction in molecular weight is more conducive to industrial production and finally high-quality rubber products are obtained. Attached Figure Description
[0053] Figure 1 The 1H NMR spectrum of the boron salt compound obtained in Example 1;
[0054] Figure 2 The isoprene homopolymer of Example 191 H NMR spectrum;
[0055] Figure 3 The GPC spectrum of the isoprene homopolymer obtained in Example 19 is shown below.
[0056] Figure 4 The DSC spectrum of the isoprene homopolymer obtained in Example 19 is shown below.
[0057] Figure 5 This is a schematic diagram illustrating the flow properties of the isoprene homopolymer obtained in Example 54;
[0058] Figure 6 This is a schematic diagram showing the flow properties of the isoprene homopolymer obtained in Comparative Example 1. Detailed Implementation
[0059] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0060] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0061] According to the present invention, the polymerization reactions are all carried out under an inert atmosphere, such as one or more inert atmospheres such as nitrogen, helium, and argon.
[0062] Preparation examples of boron salt compounds
[0063] Example 1: The preparation method of the boron salt compound in this example is as follows:
[0064] 13.4 g of sodium tetrakis(3,4,5-trifluorophenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B1, whose structure is as follows:
[0065]
[0066] Example 2: The preparation method of the boron salt compound in this example is as follows:
[0067] 13.4 g of sodium tetrakis(3,4,5-trifluorophenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B2, whose structure is as follows:
[0068]
[0069] Example 3: The preparation method of the boron salt compound in this example is as follows:
[0070] 11.6 g of sodium tetrakis(3,5-difluorophenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min, and the organic phase was separated. After drying, the solvent was removed to obtain boron salt compound B3, whose structure is as follows:
[0071]
[0072] Example 4: The preparation method of the boron salt compound in this example is as follows:
[0073] 11.6 g of sodium tetrakis(3,5-difluorophenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B4, whose structure is as follows:
[0074]
[0075] 11.6 g of sodium tetrakis(2,6-difluorophenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min, and the organic phase was separated. After drying, the solvent was removed to obtain boron salt compound B5, whose structure is as follows:
[0076]
[0077] Example 6: The preparation method of the boron salt compound in this example is as follows:
[0078] 11.6 g of sodium tetrakis(2,6-difluorophenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B6, whose structure is as follows:
[0079]
[0080] Example 7: The preparation method of the boron salt compound in this example is as follows:
[0081] 21.6 g of sodium tetrakis(2,6-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B7, whose structure is as follows:
[0082]
[0083] Example 8: The preparation method of the boron salt compound in this example is as follows:
[0084] 21.6 g of sodium tetrakis(2,6-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B8, whose structure is as follows:
[0085]
[0086] Example 9: The preparation method of the boron salt compound in this example is as follows:
[0087] 21.6 g of sodium tetrakis(2,4-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain boron salt compound B9, whose structure is as follows:
[0088]
[0089] Example 10: The preparation method of the boron salt compound in this example is as follows:
[0090] 21.6 g of sodium tetrakis(2,4-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B10, whose structure is as follows:
[0091]
[0092] Example 11: The preparation method of the boron salt compound in this example is as follows:
[0093] 21.6 g of sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.1 g of trilauramine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B11, whose structure is as follows:
[0094]
[0095] Example 12: The preparation method of the boron salt compound in this example is as follows:
[0096] 21.6 g of sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 13.6 g of N,N-hexadecylaniline hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B12, whose structure is as follows:
[0097]
[0098] Example 13: The preparation method of the boron salt compound in this example is as follows:
[0099] 13.4 g of sodium tetrakis(3,4,5-trifluorophenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B13, whose structure is as follows:
[0100]
[0101] Example 14: The preparation method of the boron salt compound in this example is as follows:
[0102] 11.6 g of sodium tetrakis(3,5-difluorophenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B14, whose structure is as follows:
[0103]
[0104] Example 15: The preparation method of the boron salt compound in this example is as follows:
[0105] 11.6 g of sodium tetrakis(2,6-difluorophenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min, and the organic phase was separated. After drying, the solvent was removed to obtain the boron salt compound B15, whose structure is as follows:
[0106]
[0107] Example 16: The preparation method of the boron salt compound in this example is as follows:
[0108] 21.6 g of sodium tetrakis(2,6-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B16, whose structure is as follows:
[0109]
[0110] Example 17: The preparation method of the boron salt compound in this example is as follows:
[0111] 21.6 g of sodium tetrakis(2,4-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B17, whose structure is as follows:
[0112]
[0113] Example 18: The preparation method of the boron salt compound in this example is as follows:
[0114] 21.6 g of sodium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate (25 mmol, 1 equiv.) and 8.9 g of tris(2-ethylhexyl)amine hydrochloride (25 mmol, 1 equiv.) were added to a reaction flask, followed by 200 mL of water and 250 mL of dichloromethane. The mixture was stirred at 25 °C for 30 min. The organic phase was separated, dried, and the solvent was removed to obtain the boron salt compound B18, whose structure is as follows:
[0115]
[0116] Catalytic conjugated diene polymerization examples
[0117] Pages 19-36 explore the effects of different boron salt compounds on the polymerization of conjugated dienes.
[0118] Example 19:
[0119] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B1 (3.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0120] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 19, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0121] Example 20:
[0122] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B2 (3.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0123] Example 21:
[0124] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B3 (3.0 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0125] Example 22:
[0126] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B4 (3.0 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0127] Example 23:
[0128] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3.0 mg, 3 μmol, 1.0 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0129] Example 24:
[0130] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B6 (3.0 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0131] Example 25:
[0132] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B7 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0133] Example 26:
[0134] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B8 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0135] Example 27:
[0136] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B9 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0137] Example 28:
[0138] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B10 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0139] Example 29:
[0140] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B11 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0141] Example 30:
[0142] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B12 (4.2 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0143] Example 31:
[0144] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B13 (2.7 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0145] Example 32:
[0146] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B14 (2.5 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0147] Example 33:
[0148] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B15 (2.5 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0149] Example 34:
[0150] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B16 (3.7 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0151] Example 35:
[0152] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B17 (3.7 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0153] Example 36:
[0154] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B18 (3.7 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0155] Examples 19, 37-43, investigate the effects of different iron catalysts on the polymerization of conjugated dienes.
[0156] Example 37:
[0157] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-1 (7.8 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0158] Example 38:
[0159] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-2 (8.6 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0160] Example 39:
[0161] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-3 (7.5 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0162] Example 40:
[0163] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-4 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0164] Example 41:
[0165] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-5 (8.0 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0166] Example 42:
[0167] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-6 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0168] Example 43:
[0169] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-8 (8.0 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0170] Examples 19, 44-51, investigate the effects of different polymerizing monomers on iron-based catalytic polymerization.
[0171] Example 44:
[0172] Under an argon atmosphere, anhydrous cyclohexane (134 mL), 1,3-butadiene (13.4 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0173] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 44, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0174] Example 45:
[0175] Under an argon atmosphere, anhydrous cyclohexane (250 mL), β-myrcene (25.6 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 500 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0176] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 45, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0177] Example 46:
[0178] Under an argon atmosphere, anhydrous cyclohexane (410 mL), β-farnesene (41.3 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 1000 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0179] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 46, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0180] Example 47:
[0181] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (10.5 mL, 105 mmol, 10500 equiv.), 1,3-butadiene (4 mL, 45 mmol, 4500 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0182] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 47, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0183] Example 48:
[0184] Under an argon atmosphere, anhydrous cyclohexane (180 mL), isoprene (10.5 mL, 105 mmol, 10500 equiv.), β-myrcene (7.8 mL, 45 mmol, 4500 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0185] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 48, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0186] Example 49:
[0187] Under an argon atmosphere, anhydrous cyclohexane (180 mL), isoprene (13.5 mL, 135 mmol, 13500 equiv.), β-farnesene (4.2 mL, 15 mmol, 1500 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0188] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 49, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0189] Example 50:
[0190] Under an argon atmosphere, anhydrous cyclohexane (180 mL), 1,3-butadiene (12 mL, 135 mmol, 13500 equiv.), β-myrcene (1.3 mL, 7.5 mmol, 750 equiv.), β-farnesene (2.1 mL, 7.5 mmol, 750 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0191] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 50, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0192] Example 51:
[0193] Under an argon atmosphere, anhydrous cyclohexane (180 mL), isoprene (6.75 mL, 67.5 mmol, 6750 equiv.), 1,3-butadiene (6 mL, 67.5 mmol, 6750 equiv.), β-myrcene (1.3 mL, 7.5 mmol, 750 equiv.), β-farnesene (2.1 mL, 7.5 mmol, 750 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min, and then the reaction was terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the clear liquid, the polymer was washed three times with ethanol, and the resulting polymer was vacuum dried at 40°C to constant weight to obtain the elastomer polymer.
[0194] Preparation of vulcanized rubber: Weigh 100 parts by weight of the elastomer polymer of Example 51, 50 parts of N324, 70 parts of fumed silica, 1.2 parts of vulcanizing agent CZ, 1.5 parts of sulfur, and 5 parts of zinc stearate, and obtain vulcanized rubber by mixing and vulcanization.
[0195] Examples 19 and 52-53 investigate the effect of different amounts of boron salt compounds on the polymerization of conjugated dienes.
[0196] Example 52:
[0197] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (9.9 mg, 10 μmol, 1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0198] Example 53:
[0199] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (1 mg, 1 μmol, 0.1 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0200] Examples 19 and 54 investigate the effect of different monomer concentrations on the polymerization of conjugated dienes.
[0201] Example 54:
[0202] Under an argon atmosphere, anhydrous cyclohexane (85 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0203] Examples 19, 55-57, investigate the effect of different reaction temperatures on the polymerization of conjugated dienes.
[0204] Example 55:
[0205] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 30 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0206] Example 56:
[0207] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 60 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0208] Example 57:
[0209] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 90 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0210] Examples 19 and 58 investigate the effects of different alkyl aluminum groups on the polymerization of conjugated dienes.
[0211] Example 58:
[0212] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triisobutylaluminum (79.3 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound B5 (3 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0213] Comparative Example 1:
[0214] Under an argon atmosphere, anhydrous cyclohexane (150 mL), isoprene (15 mL, 150 mmol, 15000 equiv.), triethylaluminum (46 mg, 0.4 mmol, 40 equiv.), iron catalyst Fe-7 (8.9 mg, 10 μmol, 1 equiv.), and boron salt compound (3.66 mg, 3 μmol, 0.3 equiv.) were added sequentially to a 250 mL Schlenk tube. Polymerization was carried out at 40 °C for 60 min. The reaction was then terminated with 25 mL of a mixed solution of methanol and hydrochloric acid (MeOH / HCl volume ratio = 50 / 1) and 1 mL of an antioxidant. After discarding the supernatant, the polymer was washed three times with ethanol. The resulting polymer was then vacuum dried at 40 °C to constant weight to obtain the elastomer polymer.
[0215] Preparation of vulcanized rubber: Weigh 100 parts by mass of the elastomer polymer of Comparative Example 1, 50 parts by mass of N324, 70 parts by mass of fumed silica, 1.2 parts by mass of vulcanizing agent CZ, 1.5 parts by mass of sulfur, and 5 parts by mass of zinc stearate. After mixing and vulcanization, vulcanized rubber is obtained.
[0216] The chemical structure is shown below:
[0217]
[0218] Table 1 Test data of conjugated diene homopolymer elastomer
[0219]
[0220]
[0221] Table 2 Test data of conjugated diene homopolymer elastomers
[0222]
[0223] Table 3 Test data for conjugated diene homopolymer elastomers
[0224]
[0225] Table 4 Test data of conjugated diene homopolymer elastomer
[0226]
[0227] Table 5 Test data for conjugated diene copolymer elastomers
[0228]
[0229]
[0230] Table 6 Test data for conjugated diene copolymer elastomers
[0231]
[0232] Table 7 Test data for conjugated diene copolymer elastomers
[0233]
[0234] Table 8 Test data for conjugated diene copolymer elastomers
[0235]
[0236] Table 9 Test data for conjugated diene copolymer elastomers
[0237]
[0238] Note: In Tables 1-9, IP represents isoprene, BD represents butadiene, MY represents myrcene, and FA represents farnesene.
[0239] Table 10 Test data of vulcanized rubber performance
[0240]
[0241]
[0242] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A boron salt compound, characterized in that, The general structural formula is: In the formula, R1, R2, R3, R4, and R5 are each independently selected from one of H, F, Cl, and CF3, and R1, R2, R3, R4, and R5 are not all H at the same time; R6, R7, and R8 are each independently selected from one of phenyl, substituted phenyl, and C6-C30 straight-chain or non-straight-chain alkyl, and the total number of carbon atoms in R6, R7, and R8 is ≥20.
2. The boron salt compound according to claim 1, characterized in that, Boron salt compounds are selected from one of formulas B1 to B18:
3. The method for preparing the boron salt compound according to claim 1 or 2, characterized in that, The method described: Water and an organic solvent were added to a tetraphenylborate metal salt containing R1, R2, R3, R4, and R5 substituents and an organic amine salt containing R6, R7, and R8 substituents. The mixture was stirred and reacted. After separation, the organic phase was dried and the solvent was removed to obtain the boron salt compound.
4. The method according to claim 3, characterized in that, The tetraphenylborate metal salt containing R1, R2, R3, R4, and R5 substituents is the same as that in claim 1, and the tetraphenylborate metal salt is at least one of lithium, sodium, and potassium salts; the organic amine salt containing R6, R7, and R8 substituents is the same as that in claim 1, and the organic amine salt is at least one of organic amine hydrochloride, organic amine sulfate, and organic amine nitrate; the organic solvent is one or more of n-hexane, cyclohexane, dichloromethane, toluene, and ethylbenzene; the molar ratio of the substituted tetraphenylborate metal salt to the substituted organic amine salt is (1-3):1; the stirring reaction temperature is 0-100℃; and the stirring time is >5 min.
5. The application of the boron salt compound according to claim 1 or 2 as a co-catalyst in iron-catalyzed conjugated diene polymerization, characterized in that, The polymerization method steps are as follows: Under anhydrous and oxygen-free conditions, solvent, conjugated diene monomer, alkyl aluminum, iron catalyst and boron salt compound are added sequentially to the reactor. The polymerization reaction is carried out by stirring at 0-100℃ for 10-120 min. After the reaction is completed, quencher and anti-aging agent are added. After washing, the mixture is vacuum dried to constant weight to obtain the conjugated diene polymer.
6. The application according to claim 5, characterized in that, The general structural formula of iron catalysts is: Among them, R9, R 10 It is one of hydrogen, alkyl, substituted alkyl, aryl, or substituted aryl, where X is EHA- or NDA-, and EHA- is... NDA - for Alkyl aluminum is one or more of the following: diethylaluminum monochloro, diethylaluminum dichloro, trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, triisobutylaluminum, triisopropylaluminum, and diisobutylaluminum hydride; The conjugated diene monomer is at least one of 1,3-butadiene, isoprene, and bio-based terpenes, wherein the bio-based terpenes are monoterpenes or sesquiterpenes; The solvent is one or more of toluene, xylene, chlorobenzene, petroleum ether, n-hexane, and cyclohexane.
7. The application according to claim 6, characterized in that, Iron catalysts have one of the following structures: The alkylaluminum is one or more selected from triethylaluminum and triisobutylaluminum. Triethylaluminum is the most preferred. The monoterpene is at least one of α-myrcene and β-myrcene, and the sesquiterpene is at least one of α-farnesene and β-farnesene; The solvent is cyclohexane.
8. The application according to claim 5, characterized in that, The volume ratio of solvent to monomer is (1-15):1; the molar ratio of monomer to iron in iron catalyst is (100-50000):1; the molar ratio of boron in boron salt compound to iron in iron catalyst is (0.1-20):1; the molar ratio of aluminum in alkylaluminum to iron in iron catalyst is (10-100):1; the reaction temperature is 30-90℃, and the reaction time is 30-120 min.
9. The application according to claim 8, characterized in that, The volume ratio of solvent to monomer is (3-10):1; the molar ratio of monomer to iron in iron catalyst is (1000-25000):1; the molar ratio of boron in boron salt compound to iron in iron catalyst is (0.1-1):1; the molar ratio of aluminum in alkylaluminum to iron in iron catalyst is (20-60):
1.
10. The rubber material obtained by the application method according to claim 5, characterized in that, The number-average molecular weight of the rubber material is 200,000 g / mol to 1,000,000 g / mol, the molecular weight distribution is 1.5 to 5.0, the molar content of 3,4-structure in the conjugated diene polymer unit is 30 to 80% and / or the molar content of 1,2-structure is 30 to 60%, and the glass transition temperature of the raw rubber is in the range of -80 to 10℃.
11. The vulcanization method for the rubber material according to claim 10, characterized in that, The method described: Weigh out 100 parts of conjugated diene polymer, 50-150 parts of silica, 1-60 parts of carbon black, 1-3 parts of vulcanizing accelerator, 0.1-10 parts of vulcanizing agent, and 1-5 parts of zinc stearate by mass, mix and knead.
12. The vulcanization method according to claim 11, characterized in that, The carbon black is one or more of N660, N550, N324, N330, and N110, the vulcanizing accelerator is one or more of TMTD, CZ, M, ZDMC, and ZBX, and the vulcanizing agent is sulfur.
13. The vulcanized rubber obtained by the method of claim 11 or 12, characterized in that, The vulcanized rubber has a tensile strength >16MPa, an elongation at break >300%, and a stress at 300% elongation >6MPa.
14. The application of the vulcanized rubber of claim 13 in tire manufacturing, noise reduction, damping, and shock absorption.